2016
DOI: 10.1080/14397595.2016.1213940
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy in patients with hip osteoarthritis: Effect on hip muscle strength and safety aspects of exercise—results of a randomized controlled trial

Abstract: The Tübingen exercise therapy approach has shown to have a significant positive effect on HMS. Its implementation has shown to be feasible and safe according to the percentage of exercise participation and the absence of sustainable adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
5
19
0
1
Order By: Relevance
“…None of the studies showed between‐group difference for changes in leg extensor power (Juhakoski et al, ) or isokinetic concentric muscle strength of the knee and hip muscles (Svege et al, ). Conversely, a more recent study (Steinhilber, Haupt, Miller, Janssen, & Krauss, ) showed that strengthening exercises with the use of elastic bands supervised once weekly for 12 weeks versus no exercise resulted in a significant positive effect on hip muscle strength. However, in that study, it was not stated that outcome assessors were blinded to group allocations.…”
Section: Discussionmentioning
confidence: 95%
“…None of the studies showed between‐group difference for changes in leg extensor power (Juhakoski et al, ) or isokinetic concentric muscle strength of the knee and hip muscles (Svege et al, ). Conversely, a more recent study (Steinhilber, Haupt, Miller, Janssen, & Krauss, ) showed that strengthening exercises with the use of elastic bands supervised once weekly for 12 weeks versus no exercise resulted in a significant positive effect on hip muscle strength. However, in that study, it was not stated that outcome assessors were blinded to group allocations.…”
Section: Discussionmentioning
confidence: 95%
“…Significant improvements in pain (VAS/WOMAC) and function (WOMAC) Steinhilber B et al 136) Patients with hip OA (n=70)…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EMG activity of the GMed was significantly increased 109,120,124) . In terms of treatment of hip OA, physiotherapy and manual therapy involving the hip abductors significantly improved hip function and relieved pain (Table 8) [134][135][136] .…”
Section: Prp Injectionmentioning
confidence: 99%
“…Despite the generally positive effects of exercise on muscle strength and physical function in hip OA (10)(11)(12)(13)(14) and in patients with groin pain (15,16), exercise has only attracted little attention as a treatment to relieve symptomatic HD. Moreover, improving hip muscle strength preoperatively may be an effective way to optimize function and the outcome of PAO (17,18).…”
mentioning
confidence: 99%